Relationship Between Pregnant Women’s Knowledge of Iron Tablets and Adherence to Iron Tablet Consumption at Saritani Health Center - Deisylia Karim; Sulistiyah Sulistiyah; Reny Retnaningsih (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Anemia is a common condition among pregnant women, often caused by insufficient iron intake or poor absorption due to digestive issues. This condition can have serious implications for both maternal and fetal health. The primary objective of this study was to explore the relationship between pregnant women’s knowledge about iron tablets and their adherence to the prescribed regimen at Saritani Health Center. This study utilized a quantitative approach with a cross-sectional design. The population for this study consisted of all pregnant women visiting Saritani Health Center, with a sample size of 78 women selected through purposive sampling, based on predetermined inclusion criteria. The study’s findings indicated that the majority of respondents had a sufficient level of knowledge regarding the importance of iron tablets. A statistical analysis using the Spearman Rank test revealed a very strong correlation between the level of knowledge about iron tablets and adherence to their consumption, with a correlation coefficient of rs = 0.812 and a p-value of 0.000 (p < 0.05). This suggests that the higher the level of knowledge about iron tablets among pregnant women, the greater their compliance with taking these supplements. The study also found that while most respondents had sufficient knowledge about iron tablets, their compliance was moderate, which highlights the importance of ongoing education and support. The results of this study emphasize the critical role that knowledge plays in improving compliance with iron supplementation among pregnant women. Health education initiatives targeting pregnant women should focus on increasing awareness and understanding of the benefits of iron supplementation to prevent anemia and its associated risks. This study calls for enhanced counseling and educational efforts at the community health level to ensure better maternal health outcomes.